Language contact in a postcolonial setting : the linguistic and social context of English and Pidgin in Cameroon - Anchimbe, Eric A. (Language Contact and Bilingualism LCB, 2012)
This timely book brings together research on the features and evolution of Cameroon English and Cameroon Pidgin English, approached from a variety of innovative multilingual frameworks that focus on the emergence of mother tongue speakers. The authors illustrate how language and population contact, history (colonialism), multilingualism, translation, and indigenization have contributed to shaping the norms of postcolonial Englishes and Pidgins. Employing naturalistic data, the volume provides a new fascinating perspective that better situates and supplements existing research in the fields of African Englishes and Creolistics. It is particularly of key interest to sociolinguists, contact linguists, Africanists, Anglicists, creolists and historical linguists.